FAKE NEWS AND CIVIL LIABILITY: A STUDY ON THE IMPACTS OF DISINFORMATION DURING THE COVID-19 PANDEMIC IN BRAZIL (CIPEEX, 2024)
THIS SUMMARY TAKES A DEEPER LOOK AT THE IMPACTS OF DISINFORMATION DURING THE OUTBREAK OF THE NOVEL CORONAVIRUS IN BRAZIL, WITH A FOCUS ON THE ANALYSIS OF CIVIL LIABILITY. THE MAIN OBJECTIVE OF THIS PAPER IS TO INVESTIGATE THE LEGAL IMPLICATIONS OF THE SPREAD OF FAKE NEWS IN THE MIDST OF THE PUBLIC HEALTH CRISIS THAT HAS DEVASTATED BRAZIL AND THE WORLD. THE CENTRAL AIM OF THIS RESEARCH IS TO ANALYZE THE LEGAL AND SOCIAL CONSEQUENCES OF DISSEMINATION. IN THE BRAZILIAN SCENARIO, FAKE NEWS WAS PREVALENT. IT SEEKS TO UNDERSTAND HOW DISINFORMATION AFFECTED THE CIVIL LIABILITY OF THE PARTIES INVOLVED AND HOW THE BRAZILIAN LEGAL SYSTEM RESPONDED TO THESE CHALLENGES. THE METHODOLOGICAL APPROACH ADOPTED WAS ANALYTICAL AND BASED ON AN EXTENSIVE REVIEW OF CASES OF THE SPREAD OF FAKE NEWS DURING THE PANDEMIC AND THEIR RELATIONSHIP WITH THE LEGISLATION IN FORCE IN BRAZIL. THE STUDY EXAMINED A WIDE VARIETY OF SOURCES, INCLUDING COURT DECISIONS, LAWS, REGULATIONS AND HIGH-PROFILE CASES IN THE MEDIA. THE ANALYSIS REVEALED THAT THE SPREAD OF DISINFORMATION DURING THE COVID-19 PANDEMIC IN BRAZIL HAD SIGNIFICANT IMPACTS ON VARIOUS SPHERES OF SOCIETY. THIS INCLUDED DAMAGE TO THE REPUTATION OF PEOPLE AND INSTITUTIONS, SOCIAL PANIC AND, IN SOME CASES, EVEN THE LOSS OF LIVES DUE TO INCORRECT INFORMATION ABOUT TREATMENTS AND PREVENTIVE MEASURES. CIVIL LIABILITY EMERGED AS A CENTRAL ISSUE IN THIS CONTEXT. THE STUDY IDENTIFIED CASES IN WHICH INDIVIDUALS, GROUPS AND MEDIA OUTLETS WERE HELD LEGALLY RESPONSIBLE FOR DISSEMINATING FALSE INFORMATION THAT CAUSED HARM TO THIRD PARTIES. THE ANALYSIS OF THESE CASES INDICATED THAT THE BRAZILIAN LEGAL SYSTEM HAS STRUGGLED TO HOLD THE AUTHORS OF FAKE NEWS ACCOUNTABLE, ESPECIALLY WHEN THERE IS SUBSTANTIAL DAMAGE. THIS STUDY CONCLUDES THAT DISINFORMATION DURING THE COVID-19 PANDEMIC IN BRAZIL HAS HAD PROFOUND IMPLICATIONS, NOT ONLY IN THE SOCIAL SPHERE, BUT ALSO IN CIVIL LIABILITY. THE BRAZILIAN LEGAL SYSTEM HAS SHOWN FLEXIBILITY IN ADAPTING EXISTING LAWS TO ADDRESS THE SPREAD OF FAKE NEWS, ALTHOUGH THERE ARE SIGNIFICANT CHALLENGES IN IDENTIFYING AND PROSECUTING THOSE RESPONSIBLE. THE RESEARCH HIGHLIGHTS THE IMPORTANCE OF ADOPTING A BROADER AND MORE EFFECTIVE APPROACH TO COMBATING THE SPREAD OF FAKE NEWS, INVOLVING COLLABORATION BETWEEN THE PUBLIC SECTOR, SOCIAL MEDIA PLATFORMS AND CIVIL SOCIETY. IN ADDITION, PUBLIC EDUCATION ON HOW TO IDENTIFY AND DEAL WITH FALSE INFORMATION IS KEY TO MITIGATING THE DAMAGING IMPACTS OF DISINFORMATION.
Keywords: Fake News; Civil Liability